2016
DOI: 10.2116/analsci.32.367
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Mutation-Discrimination Threshold for Rare Point Mutations by a Separation-Free Ligase Detection Reaction Assay Based on Fluorescence Resonance Energy Transfer

Abstract: We previously developed a separation-free ligase detection reaction assay based on fluorescence resonance energy transfer from a donor quantum dot to an acceptor fluorescent dye. This assay could successfully detect one cancer mutation among 10 wild-type templates. In the current study, the mutation-discrimination threshold was improved by one order of magnitude by replacing the original acceptor dye (Alexa Fluor 647) with another fluorescent dye (Cyanine 5) that was spectrally similar but more fluorescent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
(25 reference statements)
1
11
0
Order By: Relevance
“…The mutation-discrimination threshold obtained in the present study (5%) was in between those reported in two previous studies (1% 22 and 10% 23 ) that used a quantum dot FRET donor. Although the study that used Cy5 as a FRET acceptor featured a slightly lower threshold (1%) than that of the current study, 22 the streptavidin-coated quantum dots needed to be incubated within the post-LDR solution for 30 min to allow the quantum dots to conjugate to the 3′-biotinylated LDR product labeled with Cy5 at the 5′-end through biotin-streptavidin interactions. This post-LDR treatment was much simpler than the sequential treatments involved in the above-mentioned assay using the microbeads.…”
Section: Comparison With Previous Studiessupporting
confidence: 82%
See 3 more Smart Citations
“…The mutation-discrimination threshold obtained in the present study (5%) was in between those reported in two previous studies (1% 22 and 10% 23 ) that used a quantum dot FRET donor. Although the study that used Cy5 as a FRET acceptor featured a slightly lower threshold (1%) than that of the current study, 22 the streptavidin-coated quantum dots needed to be incubated within the post-LDR solution for 30 min to allow the quantum dots to conjugate to the 3′-biotinylated LDR product labeled with Cy5 at the 5′-end through biotin-streptavidin interactions. This post-LDR treatment was much simpler than the sequential treatments involved in the above-mentioned assay using the microbeads.…”
Section: Comparison With Previous Studiessupporting
confidence: 82%
“…This mutation-discrimination threshold is moderate, compared with our recent studies (0.25 -10%), which also used FRET for selective detection of the LDR products. [22][23][24] However, in previous studies, streptavidin-coated microbeads 24 and quantum dots, 22,23 which served as the target concentrator and FRET donor, respectively, needed to be incubated within post-LDR solution to capture the 3′-biotinylated LDR product through biotin-streptavidin interactions. Therefore, the current method can be used to examine the presence of sporadic mutations more rapidly and conveniently than previous methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hagihara et al reported a separationfree ligase detection reaction assay based on fluorescence resonance energy transfer from a donor quantum dot to an acceptor fluorescent dye. 5 This assay could successfully detect one cancer mutation among 10 wild-type templates. The mutation-discrimination threshold was improved by one order of magnitude by replacing the original acceptor dye (Alexa Fluor 647) with another fluorescent dye (Cyanine 5).…”
mentioning
confidence: 99%